Cancer-Associated Mutations in Normal Colorectal Mucosa Adjacent to Sporadic Neoplasia. Issue 7 (21st July 2020) - Zhan, Tianzuo; Belle, Sebastian; Valentini, Erica; Herrmann, Simon; Miersch, Thilo; Li, Moying; Gaiser, Timo; Boutros, Michael; Ebert, Matthias P.; Betge, Johannes
Abstract : INTRODUCTION: Colorectal cancer arises in a multistep process of carcinogenesis from normal mucosa. The earliest precursor might be a morphologically inconspicuous precancerous field, harboring cancer-associated mutations. METHODS: We systematically analyzed genetic alterations in 77 tissue samples from 30 patients with sporadic colorectal neoplasms (18 large adenomas and 12 adenocarcinomas) and matched adjacent normal mucosa (N = 30), as well as normal rectal tissue (N = 17). We profiled mutations associated with colorectal cancer by targeted sequencing of 46 genetic loci using 157 custom amplicons and a median depth of 42, 655 reads per loci. RESULTS: Multiple mutations were found in colorectal neoplasms, most frequently in APC, KRAS, and TP53. In a subgroup of 11 of 30 patients, alterations were also detected in non-neoplastic mucosa. These mutations were divergent from those in matched neoplasms. The total alteration count and the allele frequency of mutations were higher in neoplasms compared with those in adjacent tissues. We found that younger patients (≤70 years) are less likely affected by mutations in non-neoplastic mucosa than older patients (>70 years, P = 0.013), although no association was found for other variables, including type, location and differentiation of neoplasia, and previous history of polyps. DISCUSSION: Our data show that cancer-associated mutations can be found in non-neoplastic tissues in a subgroup of patients with colorectal neoplasms. Further studies are needed to specify the risk of occurrence and recurrence of neoplasia in this patient population.